Thalamic neurodegeneration in multiple sclerosis. - Cifelli, A; Arridge, M; Jezzard, P; Esiri, M; Palace, J; Matthews, P (2002)
Multiple sclerosis is still regarded primarily as a disease of the white matter. However, recent evidence suggests that there may be significant involvement of gray matter. Here, we have used magnetic resonance imaging and magnetic resonance spectroscopy in vivo and histopathology postmortem to estimate thalamic neuronal loss in patients with multiple sclerosis. Our results show that neuronal loss in multiple sclerosis can be substantial (30-35% reduction). We conclude that a neurodegenerative pathology may make a major contribution to the genesis of symptoms in multiple sclerosis.